The impact of psychological ownership on employee retention in mergers and acquisitions - Degbey William Y.; Rodgers Peter; Kromah Momo D.; Weber Yaakov (Elsevier, 2023)
Research has demonstrated that turnover rates among employees and executives in the acquired firm are much higher during an M&A event. Recent empirical and review articles on M&A have also shown that employee retention/turnover can best be understood by looking at psychological attributes and perceptions of M&As, thus drawing significant attention to the psychological and ‘human’ side voids to theoretically exploit and enhance understanding of people-related problems in M&A endeavors. In this article, we develop a moderated mediation model and propose that acquired firm employees’ psychological ownership is positively related to acquired firm employees’ retention through the direct and mediating effects of employees’ commitment and involvement in M&A. We also propose that the effect of acquired firm employees’ psychological ownership on employees’ commitment and involvement and, ultimately, acquired firm employees’ retention is moderated by loss of acquired firm autonomy. We also discuss implications for theory and practice, as well as future research directions of such an employees’ psychological ownership perspective on retention effects.